Smart Learning Environment Era Society 5.0: Integrasi Laboratorium Alam dan Laboratorium Buatan dalam Pembelajaran Bahasa Arab - Hanim Maziyah; Ikrimah Manjilah Auliya; M Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. Education in the Society 5.0 era is undergoing major changes. We are called upon to create a learning ecosystem that does not merely rely on technological sophistication, but also upholds human values and the real-life context. In Arabic language learning, the issue is this: if we rely too heavily on digital technology, authentic and deep interactions diminish. Sociocultural understanding becomes superficial, and the development of students’ spiritual character is also disrupted. This study aims to design a Smart Learning Environment (SLE) model that combines two types of laboratories: natural and artificial. The goal is to significantly improve Arabic language skills—including listening (istimā’), speaking (kalām), reading (qirā’ah), and writing (kitābah). The method used is qualitative with library research. We collected and synthesized various key references on innovations in Arabic language learning, cognitive theory, behaviorism, and the philosophy of Islamic education. The research results indicate that natural laboratories have the advantage of providing authentic language input, vibrant socio-cultural interactions, context-appropriate communication, and character development through direct experiences in Islamic boarding schools, mosques, markets, or other social environments. Meanwhile, artificial laboratories—which utilize AI, gamification, VR, and adaptive applications—reinforce learning through digital scaffolding, structured repetition, immediate feedback, as well as flexibility in terms of time and location. When these two elements are combined, a balanced learning ecosystem is formed. The result is not only strong linguistic competence, but also improved communicative performance and spiritual awareness. This model is fully aligned with the vision of Society 5.0, which positions technology as a human-centered tool for holistic education. Keywords: Smart Learning Environment, Society 5.0, Natural Laboratory, Artificial Laboratory, Arabic language skills Abstrak. Pendidikan di era Society 5.0 sedang mengalami perubahan besar. Kita dituntut menciptakan ekosistem belajar yang tidak hanya mengandalkan kecanggihan teknologi, tetapi juga tetap memegang nilai-nilai kemanusiaan dan konteks nyata kehidupan. Dalam pembelajaran bahasa Arab, masalahnya begini: kalau terlalu bergantung pada teknologi digital, interaksi yang asli dan mendalam jadi berkurang. Pemahaman sosial-budaya menjadi dangkal, dan pembentukan karakter spiritual siswa ikut terganggu. Penelitian ini ingin merancang model Smart Learning Environment (SLE) yang menggabungkan dua jenis laboratorium: alam dan buatan. Tujuannya supaya keterampilan berbahasa Arab—baik mendengar (istimā’), berbicara (kalām), membaca (qirā’ah), maupun menulis (kitābah)—bisa meningkat secara signifikan. Metode yang dipakai adalah kualitatif dengan studi pustaka (library research). Kami mengumpulkan dan menyintesis berbagai referensi utama tentang inovasi pembelajaran bahasa Arab, teori kognitif, behaviorisme, serta filsafat pendidikan Islam. Hasil penelitian menunjukkan bahwa laboratorium alam punya kelebihan dalam menyediakan input bahasa yang otentik, interaksi sosial-budaya yang hidup, komunikasi yang sesuai konteks, dan pembentukan karakter lewat pengalaman langsung di pesantren, masjid, pasar, atau lingkungan sosial lainnya. Sementara itu, laboratorium buatan—yang memanfaatkan AI, gamifikasi, VR, dan aplikasi adaptif—memperkuat pembelajaran melalui scaffolding digital, pengulangan yang terstruktur, umpan balik seketika, serta fleksibilitas waktu dan tempat. Ketika keduanya disatukan, terbentuklah ekosistem belajar yang seimbang. Hasilnya bukan hanya kompetensi linguistik yang kuat, tetapi juga performansi komunikatif dan kesadaran spiritual yang meningkat. Model ini sangat sejalan dengan visi Society 5.0 yang menempatkan teknologi sebagai alat yang berpusat pada manusia demi pendidikan yang holistik. Kata kunci: Smart Learning Environment, Society 5.0, Laboratorium Alam, Laboratorium Buatan, Keterampilan Bahasa Arab.